Ảnh hưởng của chiều dày màng và oxi không khí đến quá trình khâu mạch quang của hệ cao su butađien/clobutyl - Việt Triều, Nguyễn Thị; Hoàn, Tạ Thiện; Hiền, Lê Xuân (Vietnam Journal of Chemistry, 2014)
Photoinitiated polymerization was used to crosslink a butadiene/chlorobutyl film of different thickness. The film thickness has an influence on the rate of the photocrosslinking, as well as on the depth of cure profile. The results showed that the higher film thickness, the lower conversion of the double bonds of butadiene rubber has occurred. In the curing reaction, the 5 µm film thickness was found to polymerize 10 times faster than that of 70 µm one. After 1 second exposure upon the UV lamp, the conversion, hardness and gel fraction attained the values 22%, 0.12 and 94% for the 5 µm film thickness and 8.8%, 0.08 and 80% for the 70 µm ones. The UV- cured film was optimal at the film thickness of 20 µm. In the absence of air, the rate of the photocrosslinking of this rubber system was 3 times faster than the rate of the photocrosslinking in the presence of air